We'll never forget you, Roberto Clemente - Engel, Trudie; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc., 1996)
Traces the baseball career of the Puerto Rican who, though his life was cut short by a tragic accident, will always be remembered as an outstanding athlete and humanitarian, and the first Latin-American player to be voted to the Hall of Fame.
Has some Spanish text.
G4
Keywords: Clemente, Roberto, -- 1934-1972 -- Juvenile literature; Clemente, Roberto, -- 1934-1972.; Pittsburgh Pirates (Baseball team) -- Juvenile literature; Baseball players -- United States -- Biography -- Juvenile literature; Puerto Ricans -- United States -- Biography -- Juvenile literature; Baseball players; Puerto Ricans -- Biography